Nurzhanova A.A., Pidlinuik V., Muratova A.Ju., Berzhanova R.Zh. Abit K., Nurmagambetova A., Nurzhanov Ch., Mukasheva T.D., Bektileuova N.K. Phyoremediation Soil Contaminated with Heavy Metals Using the Bioenergy Species Miscanthus X Giganteus: Institute of Biology and Biotechnology of the Plant of the Scientific Committee of the Ministry of Education and Science of the Republic of Kazakhstan, Kazakhstan, the city of Almaty; Institute of Biochemistry and Physiology of Plants and Microorganisms of the Russian Academy of Sciences, Russia, Saratov; Institute of Biochemistry and Physiology of Plants and Microorganisms of the Russian Academy of Sciences, Saratov, Russia (Eurasian Journal of Ecology, 2018)
The contamination of soil by heavy metals is one of the important environmental problems due totheir toxicity and negative impact to human health and the environment. An effective method for cleaning the soil from xenobiotics is phytoremediation. The aim of the study was investigate the morphological morphological indicators of biomass productivity and physiological features of the bioenergy plantMiscanthus x giganteus that grow on soil contaminated with heavy metals. When M.x giganteus wasgrown on the contaminated soil from the territory of the former military site (Maili, Balkhash district, Almaty region) and mining site (Tekeli, Almaty region) it was established that the plant is resistant to heavymetals (TI ≥ 1) and possesses to phytoremediation potential. Plant absorbs from the contaminated soil 11elements (As, Pb, Zn, Co, Ni, Cr, Cu, Sr, Mn, Ba, V). The main organ of accumulation of the hazardouselements (As, Pb, Zn, Co, Ni, Cr, Cu) is the root system, and less dangerous metals (Sr, Mn, Ba, V) anddangerous toxicant Zn is the root system and in insignificant quantities the aboveground. The bioaccumulation factor, translocation factor and recovery were calculated; results showed that M.x giganteus hasthe ability to phytostabilization soil the contaminated of the hazardous heavy metals, and phytoexctraction – the more dangerous elements. It was found that the absorption of the heavy metals from the soilby plant depends from the type of soil: the absorption spectrum of the elements from the sandy soil ishigher than the absorption spectrum of elements from the loamy soil.The results obtained indicate theeffectiveness of the M.x giganteus growing for the restoration of the abandoned contaminated lands.Key words: phytoremediation, soil, heavy metals, Miscanthus x giganteus.